Analysis of restrained composite beams exposed to fire. (1st May 2021) - Martinez, Jason; Jeffers, Ann E.
Highlights: A restrained steel-concrete composite beam was examined using ABAQUS. Catenary action is affected by span, axial restraint, and load ratio. The span of the composite beam affects the failure mode of the beam. Abstract: The actions of a restrained steel-concrete composite beam exposed to fire are investigated using the finite element software ABAQUS. A parametric study is performed to examine the influence of axial restraint stiffness, beam slenderness, load level, and axial restraint location. The fire scenario is also examined, and two fires are considered including an ASTM E119 standard fire and a design natural fire. Validation of both the heat transfer and structural analyses are presented to establish confidence in the results. The validation sheds new light on the macro-modeling of composite beams comprised of beam and shell elements. Specifically, the reference of the beam elements should be positioned at the geometric centroid of the end-connection when an axial-restraint is present. The study shows that the length of the beam heavily influences the fire response of a restrained composite beam. Composite beams with short spans tend to fail in the compressive beam-column stage, while composite beams with longer spans tend to fail in the tensile catenary stage. Furthermore, conditions that are favorable for inducing catenary action include longer beam spans, increased axial restraint stiffness, increased load level, and positioning of the axial restraint near the top of the beam. Finally, the results show that, for a beam of length L, catenary action is generally developed after the deflection limit of L /20 is reached, demonstrating that care should be used when using this deflection limit to evaluate the fire resistance of restrained composite beams.